Manajemen Konflik dalam Pondok Pesantren: Pendekatan Islami untuk Penyelesaian Masalah: Penelitian - Wahyudi Widodo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Islamic boarding schools are Islamic educational institutions that play an important role in shaping the character and morals of students. However, the diversity of social, cultural, and religious backgrounds in Islamic boarding schools often triggers conflict. Conflicts can arise in various forms, such as differences of opinion between students, tension between students and caregivers, and differences in interests in managing Islamic boarding schools. If not managed properly, these conflicts can disrupt the harmony of Islamic boarding school life and reduce the effectiveness of learning. This study aims to analyze the Islamic approach to conflict management in Islamic boarding schools, by highlighting the concept of deliberation (shura), ishlah (reconciliation), ukhuwah Islamiyah (Islamic brotherhood), and justice ('adl) in resolving disputes. The research method used is qualitative with an ethnographic approach, through direct observation and analysis of documents related to conflict management policies in Islamic boarding schools. The results of the study indicate that conflict management based on Islamic values ​​can be an effective solution in maintaining the stability and harmony of Islamic boarding schools. This approach includes preventive strategies by instilling Islamic values ​​from an early age, curative strategies through mediation by kyai or ustaz, and reconstructive strategies that focus on rehabilitating relationships and evaluating pesantren policies. By applying Islamic principles in conflict resolution, pesantren can create a more conducive, harmonious educational environment that is in line with the goals of fostering the character of students